The long-term impact of wheelchair delivery on the lives of people with disabilities in three countries of the world - Susan Shore (African Journal of Disability, 2017)
Background: Lack of access to mobility for people with disabilities, particularly in less- resourced settings, continues to be widespread. Despite challenges to wheelchair delivery, the benefits to health, employment, social integration and life satisfaction are apparent. Objectives: Previous studies have explored the impact of receiving a wheelchair on the lives of the users through cross-sectional or short-term longitudinal analysis. The current study was undertaken to evaluate whether previously reported changes were sustained after 30 months of use, and whether results varied between two differing models of a wheelchair. Method: One hundred and ninety-one subjects from Peru, Uganda and Vietnam received one of two models of wheelchair provided by the Free Wheelchair Mission. Using interviews to record survey results, data were collected at the time the wheelchair was received and following 12 and 30 months of use. Variables of overall health, employment, income and travel were explored through non-parametric analysis. Results: There was a significant improvement in overall health and distance travelled after 12 months, but these changes were no longer significant by 30 months (Friedman test for overall change, p = 0.000). Employment status showed a small but significant increase at 12 and 30 months (Cochran’s Q, p = 0.000). Reported income increased slowly, becoming significantly different at 30 months (Friedman test, p = 0.033). There was no association between the model of wheelchair received and the incidence of pressure ulcers, pain or maintenance required. There was higher satisfaction with the GEN_2 wheelchair at 12 months (p = 0.004), but this difference was not apparent by 30 months. Overall wheelchair satisfaction and maintenance levels were favourable. Conclusion: While overall health status, and distance travelled into the community fluctuated over time, receipt of one of two models of a wheelchair in less-resourced settings of the world appears to have a positive sustained impact on employment and income. Further investigations should be carried out to confirm these results and explore the factors responsible for fluctuating variables. This study affirms the importance of long-term follow-up of outcomes associated with wheelchair distribution in less-resourced environments.